Emotional tourist-experience model: exploring the health-wellbeing for the active 50-plus tourists/ Anugool Bhumiwat and Ann Suwaree Ashton - Bhumiwat, Anugool; Ashton, Ann Suwaree (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2020)
This study aims to examine the emotional tourist-experience model, constructs, and their relationships towards health-wellbeing for the active 50-plus tourists. With the opportunity involving health activities while traveling, the active 50-plus have motivated themselves by setting goals of their own choices to gain the preferred meaningful experiences. The experiences that give value to their later-life well-being can drive them to continue traveling with health reasons. Five underpinned experience factors are sequentially formulated for the study model to understand tourist experience process. The model of which includes goal-driven motivation, positive emotional tourist-experience, tourist satisfaction, memorable experience and intention behaviour. To test the model, the study employed survey questionnaire for data collection and structural equation modelling for data analysis. The findings supported the causal relationships and the effect directions of those factors. The collected experience value has resulted in the individual health benefits and lifestyles of four fundamental PMSE dimensions: physical, mental, social, and emotional. The study offers the results of new mindset changing healthactivity behaviour for their later life well-being and contributes to the extended theories of motivation concerning health and well-being.